Komunikasi Transendental : Dalam Buku Panduan Sholat Khusuk Karya DR. Sa'id Bin Ali Bin Wafh Al-Qahthani - Mardiyah, Mardiyah; Syarifudin, Achmad; Aji Isnaini, Modh (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This thesis is entitled "Transcendental Communication: in the Handbook of Solemn Prayer by Dr. Said Bin Ali Bin Wahf Al-Qahthani”. This research discusses Transcendental Communication, where this research only focuses on one book, namely the book Guide to Solemn Prayer by Dr. Said Bin Ali Bin Wahf Al-Qahthani. The aim of this research is to find out what forms of transcendental communication in prayer are and to find out the meaning of transcendental communication in prayer through the book Khusyuk Prayer Guide by Dr. Said bin Ali bin Wahf Al-Qathani. This research uses semiotic theory based on transcendental communication. Data collection techniques were carried out using library research. In this research, it was found that transcendental communication is divided into two, namely verbal and non-verbal which includes movements and readings such as the meaning of takbiratul ikhram, Alfatiha, bowing, i'tidal, prostration, sitting between two prostrations, tahiyat, greetings.